Sustainability as a Real Utopia – Heuristics for transformative sustainability research. (September 2022) - Harnesk, David; Isgren, Ellinor
The idea of 'Sustainability as a Real Utopia' elaborated on here adapts sociologist Erik Olin Wright's emancipatory social science and is a heuristic informed by critical realism and social theory for interdisciplinary research on viable alternatives that move society towards achieving sustainability. Starting from the proposition that many environmental problems are rooted in how social structures and institutions interact with nature by shaping human agency, we argue for concretely situated analysis aimed at guiding human agency towards changing those root causes. Then, drawing on concrete examples from sustainability research, we elaborate on three central tasks: diagnosing and critiquing environmental problems, elaborating viable alternatives and proposing a theory of transformation. Finally, we discuss, and welcome dialogue around two central and interlinked challenges of our approach to transformative sustainability research: that of scales, and that of the distinction and relationship between reforms and transformation.